Geographical perspectives in the language of the cinema: the city of london in 007 Skyfall - Lima, Francisco Elvys Silva; Gonçalves, Tiago Estevam (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
Starting from an analysis of the film 007 - Operation Skyfall under the geographical direction, it is the objective of this study to explore the relations between geography and images from the representation of the urban space of the city of London in the cinema, through cuts of scenes. Seeking to go beyond the studies already produced, the article seeks to understand the cinematographic landscapes, interpreting them in a geographic view the elements that compose it, relate them to reality and seek to understand the factors that can enable the change in their meaning with the manipulation of the real landscapes. It is considered that the approximations between geography and cinematographic art are possible, leading the new researchers to an interdisciplinary reflection of the knowledge about the urban space of London.